Child development at 6 years after maternal cancer diagnosis and treatment during pregnancy. (October 2020) - Vandenbroucke, Tineke; Verheecke, Magali; van Gerwen, Mathilde; Van Calsteren, Kristel; Halaska, Michael J.; Fumagalli, Monica; Fruscio, Robert; Gandhi, Amarendra; Veening, Margreet; Lagae, Lieven; Ottevanger, Petronella B.; Voigt, Jens-Uwe; et al.
Abstract: Background: Data on the long-term effects of prenatal exposure to maternal cancer and its treatment on child development are scarce. Methods: In a multicenter cohort study, the neurologic and cardiac outcomes of 6-year-old children born to women diagnosed with cancer during pregnancy were compared with the outcome of children born after an uncomplicated pregnancy. Assessment included clinical evaluation, comprehensive neuropsychological testing, electrocardiography and echocardiography. Results: In total, 132 study children and 132 controls were included. In the study group, 97 children (73.5%) were prenatally exposed to chemotherapy (alone or in combination with other treatments), 14 (10.6%) to radiotherapy (alone or in combination), 1 (0.8%) to trastuzumab, 12 (9.1%) to surgery alone and 16 (12.1%) to no treatment. Although within normal ranges, statistically significant differences were found in mean verbal IQ and visuospatial long-term memory, with lower scores in the study versus control group (98.1, 95% confidence interval [CI]: 94.5–101.8, versus 104.4, 95% CI: 100.4–108.4, P = 0.001, Q < 0.001 [Q refers to the false discovery rate adjusted P value], and 3.9, 95% CI: 3.6–4.3, versus 4.5, 95% CI: 4.1–4.9, P = 0.005, Q = 0.045, respectively). A significant difference in diastolic blood pressure was found, with higher values in chemotherapy-exposed (61.1, 95% CI: 59.0 to 63.2) versus control children (56.0, 95% CI 54.1 to 57.8) (P < 0.001, Q < 0.001) and in a subgroup of 59 anthracycline-exposed (61.8, 95% CI: 59.3 to 64.4) versus control children (55.9, 95% CI: 53.6 to 58.1) (P < 0.001, Q = 0.02). Conclusions: Children prenatally exposed to maternal cancer and its treatment are at risk for lower verbal IQ and visuospatial long-term memory scores and for higher diastolic blood pressure, but other cognitive functions and cardiac outcomes were normal at the age of 6 years. Clinical trial registration: The study is registered at ClinicalTrials.gov, NCT00330447 . Highlights: Cancer treatment including chemotherapy is possible during pregnancy. Children are at risk for lower verbal IQ and visuospatial long-term memory scores. Other cognitive functions and cardiac outcomes were normal at the age of 6 years. We documented ototoxicity in three children exposed to cisplatin. Follow-up until adulthood is recommended.